Economic and Legal Problems of Banning the Sale of Agricultural Lands of State and Municipal Ownership (Bulletin of Kharkiv National University of Internal Affairs, 2021)
The article is focused on studying perspectives and problems of implementing amendments to land legislation related to the abolition of the moratorium on the sale of agricultural lands and the introduction of free circulation of these lands. The purpose of the work is to identify the main economic and legal problems that will arise in connection with the ban from July 1, 2021 on the alienation of agricultural lands of state and municipal ownership.The main problems associated with the introduction of a ban on the sale of state and municipal lands are the restriction of economic competition and equality of ownership under the law, the withdrawal of plots included in economic circulation and economic activity from the land market; creation of conditions for uncontrolled and free withdrawal of lands from state and municipal ownership by their free transfer to the ownership of citizens; underfunding of infrastructure projects of local significance.It has been offered to limit the ban on the sale of agricultural lands of state and municipal ownership in Part 7 of the Art. 130 of the Land Code of Ukraine (as amended on July 1, 2021) only to land plots that are now on the rights of land use of state and municipal enterprises, institutions and organizations and are used for statutory goals of these entities; in case of redemption of land plots of state and municipal ownership at auction by their current land user, we should introduce installment payment mechanisms for such land user in case he acquires the right to lease until 2019; to cancel the action of paragraph “b” of Part 1 of the Art. 121 of the Land Code of Ukraine concerning the free of charge transfer of land plots in the property of the ground areas for conducting personal peasant economy.The results of the study can be used in the lawmaking practice to improve land legislation in terms of the creation and operation of free circulation of agricultural lands.